Enhancing ethical self-efficacy among dementia caregiver staff: A mixed-methods feasibility study of the care programme - Lauridsen, Sigurd; Skov, Sofie Smedegaard; Ferm, Lucca-Mathilde Thorup; Berg, Marie-Eva; Folker, Anna Paldam; Simonsen, Peter; Schou-Juul, Frederik (International journal of nursing studies advances, 2025)
The global population living with dementia is rapidly increasing, with projections estimated at 78 million by 2030 and 132 million by 2050 due to ageing demographics. Despite the increasing prevalence of dementia, effective treatments remain limited. High-quality care is critical, but it presents complex ethical challenges, including balancing autonomy with best interests, addressing the needs of individuals with dementia and their caregivers, and equitably allocating resources. To address these challenges, we introduced the CARE programme, a systematic approach to ethics work, in nursing homes to enhance the ethical self-efficacy of nursing home staff. This study assessed the feasibility of the CARE programme in a community-based Danish nursing home setting. Using the framework of Bowen et al. and a mixed-methods research design, we conducted six face-to-face focus group interviews with nursing home staff, two telephone interviews with nursing home managers, and a survey among 90 participants. Data were collected in the spring and fall of 2022. Quantitative data were analysed using STATA for descriptive statistics, while qualitative data were processed using a six-step template analysis framework. The results indicate high feasibility and acceptance of the CARE programme among the nursing home staff. To a high/some degree, 97 % expressed satisfaction, 95 % found the programme relevant to their work, 90 % believed it would improve dementia care, and 82 % felt better equipped to handle ethical dilemmas. Both the management and staff acknowledged the programme's effectiveness in filling the critical gap in ethics training in nursing homes. Appreciation for external facilitation, participation from multiple nursing homes, and cross-institutional group work emphasised the value of the programme. The quantitative results indicate high levels of satisfaction and relevance, with the majority of participants believing that the program improves care and enhances their ability to manage ethical issues. Qualitative insights further emphasize the program's success in meeting the need for ethics training, facilitated by external researchers and cross-institutional collaboration. Full implementation of the CARE programme requires a cultural shift in nursing homes that advocates for universal staff involvement in ethics training and promotes open dialogue about ethical issues. Moreover, policy changes may be necessary to secure funding and establish minimum training standards for nursing home staff.